Model development and performance analysis of integrated gasification process and proton exchange membrane fuel cell - Muhammad Bilal, Muslim (2019)
The total energy demands from the entire global are increasing every day in order to support economic growth. Most of the sources of energy used are coming from fossil fuel which is non-renewable energy sources. Although there are still large supplies of fossil fuel, it is inevitable that one day the amount of fossil fuel will be decreased and running out. Hence, the renewable energy sources are currently identified as the best choice for replacing the fossil fuels as main energy supply. Palm oil wastes as the alternative for fossil fuel substitution have the potential to be utilized for energy purpose due to its abundances and availabilities in Malaysia. This biomass can be used to produce useful product such as synthesis gas which can be utilized for power production. Thus, an integrated workflow of biomass gasification and PEMFC has been developed for producing the required synthesis gas and power production. The applications of the integrated workflow are highlighted through five different case studies which each have different objectives. All five case studies are covering the model validation of fixed and fluidized bed gasifiers, performance of the gasifiers, gasification of raw and torrefied palm oil wastes, and effects of purification on the hydrogen and power production. Both models of fixed and fluidized bed gasifiers have been developed in Aspen Plus software and the validation results obtained are in good agreement with literature data. Higher amount of hydrogen gas was obtained in fluidized bed gasifier compare to fixed bed gasifier which indicates fluidized bed provides better performance for producing synthesis gas. Palm oil wastes such as Oil Palm Frond (OPF), Palm Kernel Shell (PKS), Palm Mesocarp Fiber (PMF) and Empty Fruit Bunch (EFB) have been used as inputs for both gasifiers and the simulation results show the OPF obtained 7.81 % and 5.12 % of hydrogen gas for fluidized bed and fixed bed gasifiers respectively. For synthesis gas composition, the torrefied OPF at 300 °C provides the highest hydrogen production compare to raw OPF indicating torrefaction as pre-treatment method is able to improve synthesis gas production. The effects of purification have been tested where more hydrogen gas are produced and the amount of carbon monoxide (CO) is reduced below 10 ppm which is the allowable amounts as input for Proton Exchange Membrane Fuel Cell (PEMFC). For power production, torrefied OPF at 300 °C provides the highest power produced around 5.74 kW and 6.65 kW for integrated fixed bed-PEMFC and fluidized bed-PEMFC respectively. In terms of efficiencies, for integrated fluidized bed-PEMFC, the torrefied OPF at 300 °C produces 55.88 % for electrical efficiency, 74.24 % for overall efficiency and 34.98 % for stack efficiency. Meanwhile for integrated fixed bed-PEMFC, the torrefied OPF at 300 °C produces 48.27 % for electrical efficiency, 69.47% for overall efficiency and 27.74 % for stack efficiency. In overall, the integrated gasification and PEMFC is able to be used as tools for power production and efficiency indicator and torrefaction as pre-treatment method is a useful for upgrading the hydrogen and power production.